Multiple dental retentions: literature review - Maftouh, B.; Khazana, M.; Alami, S. (International Journal of Dental Research, 2022)
Multiple dental inclusions are a relatively rare pathology. They are often part of complex dysmorphoses which require an interrogatory, clinical and radiological examination. The most frequent etiologies of inclusion are local. However, the presence of multiple inclusions can also be correlated with genetic syndromes or metabolic or hormonal pathologies, as well as idiopathic etiologies. There are as many therapeutic approaches as there are forms of inclusions; therapeutic abstention, extraction followed by prosthetic restoration or surgical-orthodontic treatment. Developing a treatment sequence, determining the appropriate anchorage, and biomechanical planning can be a challenge. The aim of our work is to establish an up-to-date state of knowledge regarding the epidemiology, etiological factors and appropriate treatment strategies for multiple dental inclusions.Â Â Â